PENGGUNAAN BAHASA BAKU DALAM DISKUSI SISWA KELAS XI MADRASAH ALIYAH IBNU KHALDUN BOBANEIGO HALMAHERA BARAT - Nada, Anwar; Laonso, Fatmawati (EDUKASI, 2022)
The research objectives are (1) to explain how the use of standard language in the discussion of class IX students of Madrasah Aliyah Ibn Khaldun Bobaneigo West Halmahera. (2) Describe the extent to which the use of standard language in the discussion of class IX students of Madrasah Aliyah Ibun Khaldun Bobaneigo West Halmahera. The method used in this research is quantitative description method. The population and sample in this study were all students of Class XI Madrasah Aliyah Ibn Khaldun Bobaneigo, North West Halmahera, totaling 25 students. Data analysis is quantitative or statistical. Based on data analysis and conclusions can be seen (1) Based on the results of the initial test, class XI students of Madrasah Aliyah Ibnu Khaldun Bobaneigo West Halmahera obtained a score range of 81- 100 very good qualifications amounted to 4 students by 20%, students who obtained a score range of 71-80 good qualifications amounted to 4 students by 20%, students who obtained a score range of 61-70 sufficient qualifications amounted to 2 students by 10%, and students who obtained a range of a score of 50-60 lacking qualifications amounted to 15 students by 50%, and (2) The final test results showed that the class XI Madrasah Aliyah Ibnu Khaldun Bobaneigo West Halmahera had been able to use standard language, students who obtained a score range of 81-100 qualified very well ( SB) as many as 5 students by 25%, students who get a score range of 71-80 good qualifications (B) as many as 5 students of the same size r 25%, students who get a score range of 61-70 are quite good (CB) as many as 15 students are 75%, and not students who get a score range of 50-60 have poor qualifications (K).